Annual changes of bone density over 12 years in an amenorrheic athlete - Zanker, C. L.; Cooke, C. B.; Truscott, J. G. (Medicine & Science in Sports & Exercise, 2004)
PURPOSE: To link annual changes of bone mineral density (BMD) over 12 consecutive years to pharmacological intervention and to fluctuations of body mass and body composition in an amenorrheic athlete. METHODS: BMD of the lumbar spine (LS) and total proximal femur (PF) were measured using dual energy x-ray absorptiometry (DXA), every 11-13 months between ages 24.8 and 36.9 yr. Body composition was assessed every 3-4 yr from a whole body DXA scan. Body mass was recorded every 3 months. For the first 5 yr of study, the subject used oral contraceptives (OC). For the subsequent 7 yr, she used estradiol skin patches (EP) with oral norethisterone. RESULTS: The first DXA scan (age 24.8 yr) revealed a low BMD at both LS and PF, with T-scores of -1.4 and -2.8, respectively. During the next 5 yr, while adhering to OC, the BMD of her LS and PF declined by 9.8% and 12.1%, respectively. Concomitantly, her body mass fell from 45.1 to 41.4 kg, her body mass index (BMI) from 16.4 to 15.0 kg.m-2, and her percent body fat from 8.3 to <4.0%. While treated with EP and norethisterone (age 29.8-33.5 yr), her LS BMD gradually increased by 9.4%, despite a further 0.8 kg decline of body mass. From age 33.8 to 36.9 yr, voluntary weight gain (2-3 kg.yr-1; total: 8.1 kg) was accompanied by an increase of her PF BMD (16.9%), with no further increase at the LS. CONCLUSION: Changes of BMD at the total proximal femur reflected changes of body mass in this subject. At the lumbar spine, BMD declined with weight loss but increased in association with transdermal estradiol treatment in the absence of weight gain.